MINERAL SUPPLEMENTATION ON BALINESE CATTLE TOWARD LEUCOCYTE DIFFERENTIAL IN FOUR TYPES OF LAND - Putra, I Putu Cahyadi; Suwiti, Ni Ketut; Ardana, Ida Bagus Komang (Buletin Veteriner Udayana, 2016)
The aims of this research were to know the effect of mineral intake on Balinese cattle that has been fed on four different types of land (rice field, grassland, garden, and forest) towards theleukocytes differential.  The research design follows a completely randomized design (CRD) usinga nested pattern on 48 males from Balinese cattle.  The cattle were grouped according to four treatments of mineral intake, namely: controls, 2.5 grams, five grams, and 7.5 grams in each type ofland.  Furthermore, the blood was taken from the auricularis superficialis vein in the third month after treatment. A blood smear was prepared using the slide method and a sample was stained withGiemsa. The blood smear was examined by leukocytes differential using battlement method with 1000x magnification. Then, the collected data were analyzed using analysis of variance and Cochran test.  The research results show that the given treatment of minerals has no change theleukocytes differential.  In contrast, the percentage of lymphocytes in the type of garden land haslower than on the type of forest, rice land and grassland, but has no differences the percentage of neutrophils, eosinophils, basophils, and monocytes in the four types of land. The conclusion isgiving to a concentration of 7.5 gram does not change the differential leukocyte Bali cattle.
Keywords: bali cattle; mineral; leucocytes differential; types of land